2021
DOI: 10.3389/fneur.2021.638903
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Hemodynamic and Clinical Response to αCGRP in Migraine Patients—A TCD Study

Abstract: Introduction: Sensitisation of the nervous system in a patient with migraine is supposed to be associated with calcitonin gene-related peptide (CGRP) activity. Therefore, the vascular response to human αCGRP (hαCGRP) could be a surrogate marker for the sensitization. We hypothesize that vascular response to hαCGRP is augmented in a patient with migraine.Methods: Twenty healthy subjects and 20 patients with migraine participated in our study. TCD was used to monitor mean arterial velocity in the middle cerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
1
10
0
3
Order By: Relevance
“…In a previous study of our research group performed in migraineurs, 24 we found a maximal decrease in vm MCA change (point 2 of the experiment) of 67.8%, and a maximal decrease in vm PCA change of 67.1% (point 2 of the experiment), regardless of the presence of aura. After comparing migraineurs (MA and MO) to controls, 6 the maximal decrease in vm MCA change (point 2 of the experiment) was 131.1% and 45.3%, respectively.…”
Section: Discussionsupporting
confidence: 52%
“…In a previous study of our research group performed in migraineurs, 24 we found a maximal decrease in vm MCA change (point 2 of the experiment) of 67.8%, and a maximal decrease in vm PCA change of 67.1% (point 2 of the experiment), regardless of the presence of aura. After comparing migraineurs (MA and MO) to controls, 6 the maximal decrease in vm MCA change (point 2 of the experiment) was 131.1% and 45.3%, respectively.…”
Section: Discussionsupporting
confidence: 52%
“…This parameter is important, as recently demonstrated during the pandemic when both physical activity levels and sleep quality dropped in migraine patients [ 23 ]. The link between oxidative stress, physical activity, and sleep quality could somehow reside in the CGRP system [ 12 , 13 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic changes related to neurotransmitters concentration, physical ac-tivity, and the associated oxidative stress are important fields of investigation in mi-graine to achieve this goal [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to a higher release of vasoactive substances (e.g., NO) by the endothelium or to an increased sensitivity of vessel smooth muscles as hypothesized by Olesen and Thomsen [ 64 , 65 ]. Previous studies found a greater MCA velocity reduction induced by a CGRP infusion in migraineurs than controls, suggesting that MA patients have a vascular tree that is more sensitive to neurogenic modulation of hemodynamics [ 66 , 67 ]. Other mechanisms have been hypothesized on the basis of an increased sensitization in MA patients, one of which relies on CGRP release from sensory neurons.…”
Section: Discussionmentioning
confidence: 99%